Silks [compact disc, unabridged] - Francis, Dick (Penguin Audio, 2008)
After a grueling trial, defense lawyer and amateur jockey Geoffrey Mason is only too happy to head to Sandown to pound a course in the saddle of a thoroughbred. But when a fellow rider is found brutally murdered, Mason's personal and professional life become entwined in a sinister fashion.